The Transverse Musculocutaneous Gracilis Free Flap: Virtual Animation–Assisted Dissection and Application in Breast Reconstruction. Issue 5 (May 2016) - Gabert, Pierre-Elliott; Bodin, Frederic; Aljudaibi, Nawaf; Duquennoy-Martinot, Veronique; Guerreschi, Pierre
Abstract : Summary: The transverse musculocutaneous gracilis free flap is a valuable choice for autologous tissue, unilateral or bilateral breast reconstruction. This procedure is an excellent and customized option for immediate or delayed breast reconstruction in patients with small to moderate size breasts. Few descriptions of flap dissection and breast mound shaping are available. In this first educational video, the authors report the original dissection of the transverse musculocutaneous gracilis free flap used for breast reconstruction. Virtual animations insist on surgical key points and relevant details of the harvesting of the flap. Abstract : Supplemental Digital Content is available in the text.